2013
DOI: 10.19030/iber.v12i6.7870
|View full text |Cite
|
Sign up to set email alerts
|

Happy In The Informal Economy? A Case Study Of Well-Being Among Day Labourers In South Africa

Abstract: Past research provided evidence of the negative effect that individual unemployment can have on subjective well-being. The persistent high levels of unemployment and poverty in South Africa INTRODUCTION AND AIM OF THE PAPERhere was a time when the study of well-being, and subjective well-being in particular, was, for the most part, excluded from economic analysis as a result of the disciplinary paradigm of logical positivism. Yet, economic theories often include reference to values, expectations, and the like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 39 publications
(37 reference statements)
2
12
0
Order By: Relevance
“…More money makes people happier because they can buy more (Coyle, 2012). Even in the case of South African day labourers in the informal economy, Blaauw, Botha, Schenck and Schoeman (2013) found that income and its increase are important in bringing about happiness, particularly when individuals are poor and live in deprived communities. In developing countries, higher income raises the happiness of poor people living below the bread line, enabling them to meet basic needs.…”
Section: Income and Happinessmentioning
confidence: 99%
“…More money makes people happier because they can buy more (Coyle, 2012). Even in the case of South African day labourers in the informal economy, Blaauw, Botha, Schenck and Schoeman (2013) found that income and its increase are important in bringing about happiness, particularly when individuals are poor and live in deprived communities. In developing countries, higher income raises the happiness of poor people living below the bread line, enabling them to meet basic needs.…”
Section: Income and Happinessmentioning
confidence: 99%
“…The study outlined in this paper expands on previous research by Blaauw et al (2013) (which looked at well-being in a general sense) by focusing specifically on the subjective wellbeing of day labourers and by introducing a new dimension: day labourers' geographical location, which is influenced by migration patterns. Migration and geographical differences are important considerations in a study of subjective wellbeing as they reflect day labourers' willingness to move from poorer to richer provinces in pursuit of greater economic opportunity and choice.…”
Section: Introductionmentioning
confidence: 89%
“…To investigate the impact of geographical location on the well-being of day labourers in South Africa, we employed a cross-sectional analysis using dummy variables for the nine provinces -which the exploratory study by Blaauw et al (2013) did not make provision for. The purpose of these dummy variables was to account for differences in the wellbeing of day labourers between provinces.…”
Section: Model Selection and Empirical Analysis Research Methodsmentioning
confidence: 99%
See 2 more Smart Citations